Expression of IL-8 Gene in Rainbow Trout (Oncorhynchus mykiss) Leucocytes Fed with Uryani plum (Prunus domestica) Extract - Akman, Nazlı Ceren; Yilmaz, Elif Melisa; Karaali, Kaan; Bilen, Soner (Kastamonu Üniversitesi Veteriner Fakültesi, 2024)
Aim to study: In the present study, interleukin-8 (IL-8) gene expression was determined in rainbow trout (Oncorhynchus mykiss) after treatment with uryani plum (Prunus domestica) extract. Material and methods: Fish leucocyte was stimulated with plum extract at the rate of 0 (control), 5 mg/ml, 10 mg/ml and 15 mg/ml. Cells were collected at 1, 4, 12, 24, and 48 hours of the study and IL-8 gene expression was determined in each group. Results: The result showed an increase in IL-8 expression in all experimental groups compared to the control at the end of the study. Conclusion: The results suggested that uryani plum (Prunus domestica) extract could activate immune responses of rainbow trout head kidney leukocytes in rainbow trout.
Keywords: Veterinary Sciences (Other); Veteriner Bilimleri (Diğer); IL-8; İmmune response; Fish; Prunus domestica; Gene expression